HOUSE OF THE DRAGON: A FEMINIST ANALYSIS OF FEMALE LEADERSHIP IN A PATRIARCHAL SOCIETY - Izzasamura, Kanaya Aurella (Serat: Journal of Literary & Cultural Studies, 2025)
Women in medieval fantasy narratives have historically been marginalized, particularly through their exclusion from political agency and representation. This feminist study examines HBO’s popular series, House of the Dragon, analyzing key characters Rhaenyra Targaryen and Alicent Hightower to uncover how systemic patriarchy shapes their leadership and political strategies. Through textual and visual analysis, this research explores women’s agency in patriarchal society, asking whether the series critiques or replicates misogyny. Findings reveal that House of the Dragon reflects misogynistic norms, such as Rhaenyra’s claim to the Iron Throne—though named heir by the previous King—is constantly challenged due to her gender. At the same time, Alicent leverages the patriarchal structure to gain political influence. House of the Dragon may intend to critique patriarchy by highlighting Rhaenyra and Alicent’s struggles and framing their power as a form of resistance. However, it inadvertently reinforces patriarchy by punishing both characters for attempting to dismantle the system.